Validation of the Abbreviated Brucella AMOS PCR as a Rapid Screening Method for Differentiation of Brucella abortus Field Strain Isolates and the Vaccine Strains, 19 and RB51 - Ewalt, Darla R. (American Society for Microbiology, 2000)
The Brucella AMOS PCR assay was previously developed to identify and differentiate specific Brucella species. In this study, an abbreviated Brucella AMOS PCR test was evaluated to determine its accuracy in differentiating Brucella abortus into three categories: field strains, vaccine strain 19 (S19), and vaccine strain RB51/parent strain 2308 (S2308). Two hundred thirty-one isolates were identified and tested by the conventional biochemical tests and Brucella AMOS PCR. This included 120 isolates identified as B. abortus S19, 9 identified as B. abortus strain RB51, 57 identified as B. abortus biovar 1, 15 identified as B. abortus bv. 2, 1 identified as B. abortus bv. 2 (M antigen dominant), 7 identified as B. abortus bv. 4, and 22 identified as B. abortus S2308 and isolated from experimentally infected cattle. The Brucella AMOS PCR correctly identified each isolate as RB51/S2308, S19, or a field strain of Brucella.